Avaliação e impacto dos efeitos adversos da terapia endócrina adjuvante em mulheres pós-menopausadas sobreviventes de câncer de mama: estudo prospectivo - Custódio, Isis Danyelle Dias (2021)
Introduction: The adjuvant treatment with Aromatase Inhibitor (AI) is considered standard of care for postmenopausal breast cancer (BC) women with hormone receptor-positive (HR+), however, it often causes adverse effects such as cancer-related fatigue (CRF), depression and musculoskeletal symptoms. Instruments to manage symptoms may improve adherence and persistence of treatment, health-related quality of life (HRQL) and health outcomes. Objective: This thesis had two main objectives: 1) To identify the relationship between serum 25-hydroxyvitamin D [25(OH)D] level and CRF, and to analyze their effects on depression, anxiety, functional disability, muscle/joint aches and HRQL; 2) To perform additional validation of the 31-item Cervantes Scale (CS-31), 16-item Cervantes Short-Form Scale (CS-16) and 10-item Cervantes Scale (CS-10). Material and Methods: This is a prospective study conducted with 89 postmenopausal women diagnosed with HR+ early BC in adjuvant endocrine therapy with AI. The assessments were performed at three time points: T0, baseline; T1, intermediate follow-up period, 12 months after T0; and T2, final follow-up period, 24 months after T0. At each time point, anthropometric and body composition assessments were performed, as well as dietary assessments by application of 24-hour dietary recall (24HR). The women completed the Cervantes Scale (CS), Hospital Anxiety and Depression Scale (HADS) and Health Assessment Questionnaire (HAQ). The CRF was measured using the subscale fatigue (FACIT-Fatigue) of the Functional Assessment of Chronic Illness Therapy-fatigue (FACIT-F), and a score below 34 was adopted as an indicator of the presence of this adverse effect. The serum 25(OH)D level was determined by electrochemiluminescence, with a cut-off above 75nmol/L adopted as an indication of sufficiency. Generalized Linear Model (GLzM) and Generalized Mixed Model (GMM) analysis were used to determine, respectively, associations and effects. A Minimum Clinically Important Difference (MCID) of 5% in FACIT-Fatigue score between the three time points was used to classify the women into five clusters of CRF: The same, better, worse, V and Inverted V. In addition, for CS, internal consistency, construct validity, responsiveness and known-group validity were evaluated. Results: Our results showed that slightly more than one-third of the BC survivors had CRF and low serum 25(OH)D levels. The women with CRF had been using AI for a shorter time when compared to the subgroup without CRF. The dietary vitamin D did not differ significantly between the subgroups of 25(OH)D, however none of the women reached the Estimated Average Requirements (EAR) of this nutrient. There were negative associations between the FACIT-Fatigue score and body adiposity. The greater percentage of women was classified as “better”, i.e with improvement in the FACIT-Fatigue score throughout the study. No significance was found regarding the direct and reverse causality between serum 25(OH)D level and CRF. Low serum 25(OH)D level had a negative effect on the scores of anxiety, of Menopause and Health domain and Vasomotor subdomain of the CS-31. In addition, women with CRF presented more anxiety, depression, functional disability, muscle/joint aches, worse HRQL and worse score in the following domains and subdomains of the CS-31 – Menopause and Health, Psychological, Vasomotor, Health, Aging and Couple Relations. These results show the clinical relevance of both serum 25(OH)D and CRF, highlighting the latter. The three CS presented adequate internal consistency and known-group validity, with statistical significance between anxiety and depression and worse HRQL, but only CS-10 and CS-31 presented satisfactory construct validity. Also, we identified a prospective improvement in HRQL, with higher scores at T0 compared to other time points. Conclusion: The clinical relevance of 25(OH)D and CRF is highlighted, especially CRF, considering theirs impact on others important adverse effects reported by these women. In addition, the negative effect of body adiposity on CRF can be confirmed in this study. The analysis of psychometric properties revealed that the CS, highlighting the CS-31, seem to be appropriate instruments for the medical routine with BC survivors during adjuvant endocrine therapy and may help to monitoring adverse effects and HRQL, although larger studies are needed to confirm these results.